Advances in Chemical Bioanalysis - Matysik, Frank-Michael (Bioanalytical Reviews, 2014)
Expert authors provide critical, in-depth reviews of available methods for retrieving selective information out of complex biological systems. Sensors, probes and devices are present and future tools of medicinal diagnostics, environmental monitoring, food analysis and molecular biology. These are based on fluorescence, electrochemistry and mass spectrometry. Coverage of this volume includes  sensor development for the detection of small analytes,  monitoring of biomolecular interactions,  analysis of cellular function,  development of diagnostic tools.